The Influence of Digital Leadership in Higher Education in Improving Academic Services - Adriantoni, Adriantoni; Vesuden, Menaga; Herawan, Endang (JURNAL AL-TANZIM, 2024)
This study aims to see the influence of digital leadership on improving academic services in higher education. This study is based on the importance of how academic services in higher education are influenced by leadership. The method used is a mixed-method approach with a sequential explanatory pattern. The data analysis technique uses descriptive statistics and SEM AMOS. The number of samples used is 242 students. The study results found that the digital leadership variable is generally in the high category. The study results found that the digital leadership variable is generally in the high category. Meanwhile, the results of the SEM AMOS test found that digital leadership significantly influences improving Academic Services, with a probability value of 0.002. This study concludes that digitalization can significantly improve academic services and accessibility, make them faster and more effective, and provide a better customer experience. The study's results are expected to be a reference for literature and a benchmark for leadership in other institutions.